A synergistic platform enables co-oxidation of halogenated organic pollutants without input of organic primary substrate. (1st May 2023) - Luo, Yi-Hao; Long, Xiangxing; Cai, Yuhang; Zheng, Chen-Wei; Roldan, Manuel A; Yang, Shize; Zhou, Dandan; Zhou, Chen; Rittmann, Bruce E.
Highlights: 4-CP was completely mineralized in an "oxidation + reduction synergistic platform" (ROSP). Over 99% of 60 mg/L 4-CP was mineralized during 15 days of continuous operation. Mineralizaation was achieved with H2 as the only external electron donor input to the ROSP. Co-oxidation of 4-CP used a primary substrate that was its reductive hydrodechlorination product. Abstract: While co-oxidation is widely used to biodegrade halogenated organic pollutants (HOPs), a considerable amount of organic primary substrate is required. Adding organic primary substrates increases the operating cost and also leads to extra carbon dioxide release. In this study, we evaluated a two-stage Reduction and Oxidation Synergistic Platform (ROSP), which integrated catalytic reductive dehalogenation with biological co-oxidation for HOPs removal. The ROSP was a combination of an H2 -based membrane catalytic-film reactor (H2− MCfR) and an O2 -based membrane biofilm reactor (O2− MBfR). 4-chlorophenol (4-CP) was used as a model HOP to evaluate the performance of ROSP. In the MCfR stage, zero-valent palladium nanoparticles (Pd 0 NPs) catalyzed reductive hydrodechlorination that converted 4-CP to phenol, with a conversion yield over 92%. In the MBfR stage, the phenol was oxidized and used as a primary substrate that supported the co-oxidation of residual 4-CP. Genomic DNA sequencing revealed that phenol produced from 4-CP reduction enriched bacteria having genes for functional enzymes for phenol biodegradation in the biofilm community. In the ROSP, over 99% of 60 mg/L 4-CP was removed and mineralized during continuous operation: Effluent 4-CP and chemical oxygen demand concentrations were below 0.1 and 3 mg/L, respectively. H2 was the only added electron donor to the ROSP, which means no extra carbon dioxide was produced by primary-substrate oxidation. Graphical abstract: Image, graphical abstract